Speech Intelligibility In Preschoolers Using Indonesian Intelligibility In Context Scale - Cindy Natalia; Hafidz Triantoro Aji Pratomo; Ari Sarwanto (Poltekkes Kemenkes Surakarta, 2022)
Background: The intelligibility in Context Scale (ICS) is one of the speech intelligibility assessment procedures that measures how clearly an individual's speech can be understood by seven different communicative partners. Recently, ICS has been translated into more than 60 languages across the world including Indonesian language. It is important to know about ICS and how to use it in Indonesia. Methods: This quantitative research is designed with a descriptive comparative method. The population of this study is preschool-aged children (4-6 years old) in Semarang City. The number of respondents in this current study is 158 respondents which consists of 20 children with parental concerns and 138 children without parental concerns. Data analysis is performed using descriptive and bivariate analysis. A Mann-Whitney U test is used for the bivariate analysis. Data collection was carried out in Semarang City in August–September 2021. Results: The total average ICS score in this study is 3.96. Children's speech is best understood by parents and least understood by strangers. There is a difference in average ICS scores for paternal education (p = 0.037), paternal income (p = 0.002), and parental concerns (p = 0.01). Conclusion: The Indonesian ICS can be used as a screening test to assess children's speech proficiency. Paternal education, paternal income, and parental concerns have a direct impact on children's average Indonesian ICS score. The lower the average Indonesian ICS score of the child, the lower his or her speech intelligibility.